2001
DOI: 10.1051/forest:2001159
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the water relations and the hydraulic characteristics in Fraxinus excelsior, Acer pseudoplatanus and A. opalus trees under soil water contrasted conditions

Abstract: -Plant water relationships and hydraulic characteristics were measured for two species of the genus Acer that co-occur with Fraxinus excelsior, but differ in their habitat preference with respect to soil moisture: Acer pseudoplatanus is restricted to wet habitats, whereas Acer opalus occurs on drier sites. The data obtained showed significantly lower hydraulic conductance and lower vulnerability to embolism in the drought-tolerant species, Acer opalus, than in the water prefering species Acer pseudoplatanus. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 19 publications
6
47
1
2
Order By: Relevance
“…This hydraulic behaviour can be related to that of F. excelsior, a species that frequently occurs with poplar trees. Ash trees have a broad ecological amplitude [16,17,23,24], the same for maple trees [31], particularly because they can acclimatize to limited water availability by increasing their resistance to cavitation [14]. As demonstrated in this study, poplar species did not have this adaptation potential of hydraulic architecture.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This hydraulic behaviour can be related to that of F. excelsior, a species that frequently occurs with poplar trees. Ash trees have a broad ecological amplitude [16,17,23,24], the same for maple trees [31], particularly because they can acclimatize to limited water availability by increasing their resistance to cavitation [14]. As demonstrated in this study, poplar species did not have this adaptation potential of hydraulic architecture.…”
Section: Discussionmentioning
confidence: 63%
“…Xylem water potentials (Ψ xylem ) were estimated by measuring the water potential of leaves that had been enclosed in aluminium foil and a plastic bag early in the morning [3,32]. Hydraulic conductivity was measured on twigs obtained from branches collected in the morning from mature trees using the procedure described by Lemoine et al [14]. The branches were enclosed in black airtight plastic bags to reduce water loss through transpiration and quickly brought to the laboratory for hydraulic analysis.…”
Section: Water Potential Stomatal Conductance and Hydraulic Conductimentioning
confidence: 99%
“…Korn (2004) reported similar values on sycamore. Lemoine et al (2001) found remarkably high (less negative) daily minima of Ψ L in A. pseudoplatanus which they explained by a high shoot hydraulic conductivity. This matches well to our findings of a particularly high root-to-leaf hydraulic conductivity in sycamore.…”
Section: Species Differences In Leaf Conductance and Leaf Water Potenmentioning
confidence: 99%
“…In F. excelsior, Lemoine et al (2001) found the minimum threshold of leaf water potential to vary between -1.5 and -2.8 MPa depending on habitat, water supply and drought acclimation. Other authors reported loss of hydraulic conductivity starting with water potentials of -2 MPa (Cochard et al, 1997;Crombie et al, 1985).…”
Section: Species Differences In Leaf Conductance and Leaf Water Potenmentioning
confidence: 99%
“…The importance of investigating hydraulic properties of trees is highlighted by recent studies showing that they may play a role in ecological strategies of species and that they can underlie the response to environmental changes [5,10]. For instance, pioneer species like Acer saccharinum and Juglans regia were vulnerable to cavitation, exhibited hydraulic segmentation and showed high hydraulic conductance (k), whereas established species like Quercus species and Pinus contorta were less vulnerable and presented a relatively low k [23].…”
Section: Introductionmentioning
confidence: 99%